PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR SISWA DI SMP NEGERI 4 SUNGAI RAYA - Arjuna Eko Saputra; Aminuyati Aminuyati; Agus Sastrawan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was aimed to explain whether the Discovery Learning has an influence on students’ achievement at SMP Negeri 4 Sungai Raya Kabupaten Kubu Raya. This research is used descriptive quatntitative mehtod with two variables namely the dependent variable (X) and the independent variable (Y) that is X= Discovery Learning as a model , and Y = Learning Outcome. The research subjects were seven grade students of SMP Negeri 4 Sungai Raya Kabupaten Kubu Raya. The technique and data collection was done by using questionnaires, observation and documantation. Based on the data analaysis which is the researcher did use a simple linear regression test, it was concluded that: 1) The implementation of the Discovery Learning as a model in SMP Negeri 4 Sungai Raya. it showed well and accordance with procedure that should be. 2) Learnng outcomes were very good because the average of all students were 82% and 96% got the score with specified. 3) Discovery Learning as a model (X) was influence learning outcome (Y) showed by the calculate F value of 202.230 > F table= 3.10 with an error rate of 5% and significance level of 95%. 4) The magnitude of the influence of the Discovery Learning Learning model on student learning outcomes, namely 68.3% in the range of 60-80% where it showed that the influence of Discovery Learning was categorized as high / strong. Keywords: Discovery Learning, Learning Outcomes.